Assessment of the correlation between Pharyngeal Airways and Palatal Index in different skeletal growth patterns - Hlushko, Ivan; Flis, Petr (The Ukrainian Scientific Medical Youth Journal, 2025)
In the discipline of orthodontics, a person's face structure can be ascertained through the specific characteristics and anatomical correlations of the palate depth, width, and airway dimensions, which aid in the identification of malocclusions. A greater awareness of the relationship between upper airway structure and sleep disordered breathing, as well as the relationship between this condition and craniofacial morphology in general, has led to a gradual increase in interest in upper and lower airway dimensions over the past few decades. The study comprised 30 participants, with a mean age of 17.5 years. Skeletal classes I, II, and III were assigned to the participants based on their ANB (A point, nasion, B point) angle (N = 10). The study models were used to calculate the palatal height, palatal breadth, and palatal height index using Korkhaus analysis. McNamara Airway Analysis was used to measure the upper and lower pharyngeal airway dimensions based on the lateral cephalogram. The ANOVA test was used to calculate the findings. For the palatal index and airway dimensions, there was a statistically significant difference observed in all three groups of malocclusions (class I, II, and III). The subjects with skeletal class II malocclusion showed the highest mean palatal index values (P=0.03). For the upper airway, class I had the greatest mean value (P=0.041), while class III had the highest mean value (P=0.026) for the lower airway. It was concluded that subjects with the class II skeletal pattern have a high palate and reduced upper and lower airways when compared with class I and class III skeletal patterns, which showed larger upper and lower airways, respectively.